Challenges faced by mental health nurses working with people living with mental illness in Eswatini: A qualitative study - Phetsile G. Zwane; Mduduzi Colani Shongwe; Fortunate S. Shabalala (Elsevier, 2022)
Background: Research on the challenges faced by mental health nurses working in poorly resourced settings, especially in Eswatini, is limited. As a result, we conducted this study to explore and describe the challenges faced by mental health nurses working with people living with mental illness in Eswatini. Methods: The study employed a qualitative approach, using an exploratory-descriptive design and the data were collected from nine (9) purposively selected mental health nurses at the National Psychiatric Referral Hospital (NPRH). A majority (n = 7) of the participants had bachelors' degrees and were female (n = 5), with a mean of 6 years working experience in a mental health setting. The data were collected using an unstructured interview guide through audio-recorded individual in-depth-interviews, and were analysed manually using Colaizzi's method of phenomenological analysis. Results: Five themes emerged from the data: i) physical violence; ii) sexual harassment iii) emotional distress due to verbal abuse; iv) stigma and discrimination; and v) administrative challenges (drug stock-outs, staff shortage, overcrowding, and inadequate infrastructure and medical equipment). Conclusion: The mental health nurses shared several challenges they encounter on their day-to-day job, including physical, psychological and administrative challenges. There is a need for the Ministry of Health working with the Wellness Centre for health workers to design staff wellness programs aimed at mitigating work-related stress and challenges faced by mental health nurses. The Ministry of Health and the NPRH administration should put in place safety measures at the NPRH and should devise a management strategy to tackle the administrative challenges raised by the nurses in this study.